Conference Report: Pittcon 2013: microfluidics, electrochemistry, and much much more. (August 2013) - Shin, Mimi; Kaplan, Sam V; Newby, Maxwell; Johnson, Michael A
The Pittsburgh Conference on Analytical Chemistry and Applied Spectroscopy, also known as Pittcon, is the world's largest annual conference and exposition based on measurement science and instrumentation. Each year, more than 18, 000 worldwide participants, coming mostly from academia, industry and government agencies, attend Pittcon to exchange information on the latest analytical techniques, the most advanced instrumentation and the current job market. In 2013, the 64th Pittcon Conference was held at the Pennsylvania Conference Center in Philadephia, PA, USA. Herein, we highlight just a few of the many presentations that describe creative and transformative research efforts aimed at obtaining bioanalytical measurements that enhance knowledge of living systems and improve human health.